BCEC Quarterly Economic Commentary, December 2017 - Cassells, Rebecca; Duncan, Alan; Kiely, Daniel (Bankwest Curtin Economics Centre, 2017)
This is the first of Bankwest Curtin Economics Centre’s Western Australia Quarterly Economic Commentary analysing the most recent data on economic and social indicators for WA.